Investogation of star-shaped poly[2-(dimethylamino)ethyl methacrylate] for forward osmosis application - Sim, Zhen Chao (2015)
Poly[2-(dimethylamino)ethyl methacrylate] (PDMAEMA) has massive potential in becoming widely used as a draw solute for forward osmosis application. Its solubility can be tuned by its carbon dioxide concentration. The recoverability can be eased just by bubbling nitrogen, argon or air into the solution at a slightly elevated temperature. This useful characteristic tackled the intrinsic problem of low energy recovery encountered in many draw solutes. However, the major obstacle hindering the usage of linear PDMAEMA polymers as draw solutes is its low water flux. The effect of changing the structure of PDMAEMA from linear to star-shaped on the water flux was examined in this report. Linear, octafunctional and trifunctional PDMAEMA polymers were synthesized using atom transfer radical polymerization (ATRP) method and their molecular weights were characterized using Nuclear Magnetic Resonance (NMR) spectroscopy. Octafunctional PDMAEMA produced the highest amount of water flux among the different star-shaped and linear polymers with similar molecular weight synthesized with 0.415LMH at a concentration of 0.3g/g, double of the next highest water flux generated. In addition, the inverse relationship between water flux and molecular weight for trifunctional and octafunctional polymers was also confirmed in this study. As a consequence, star-shaped polymers are more promising than linear ones for usage as draw solute due to higher flux at similar molecular weights. This study also provides a direction for future research on polymer draw solutes to focus on star-shaped ones as molecular weight will be further decreased in order to find the smart draw solute for forward osmosis application.